A test of the CAPM on Philippine common stocks - Yu, Joel C. (2002)
This paper presents the results of an empirical test of the capital asset pricing model (CAPM) on the returns on Philippine common stocks from 1990 to 2000. The test uses the two-step cross sectional regression (CSR) procedure to compute for the beta of each asset and the parameters of the Sharpe-Lintner version of the CAPM. The basic data used in the study consist of average monthly returns of 50 representative common stocks drawn from a stratified random sampling process. Test results show that there are sub-periods that support the predictions of the CAPM, but other sub-periods yield results that run counter to the CAPM predictions. These results are unaltered after incorporating the Shanken correction factor that addresses the error-in-variables problem inherent in CSR. Further tests also show that, in the short run, factors other than risk explain the cross section of asset returns and that the relationship between return and risk may not be linear.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 140-141).
Keywords: Capital assets pricing model; Investments -- Mathematical models; Stocks -- Prices -- Philippines